The study of bonding behavior between fiber reinforced polymer composite plate and concrete prism under tropical climate - Ismail, Yob Saed; Mohd. Sam, Abdul Rahman; Abu Hassan, Shukur (Universiti Teknologi Malaysia, 2003)
Carbon Fibre Reinforced Polymer (CFRP) composites have been used successfully as strengthening material for reinforced concrete structures by externally plate-bonded technique. The CFRP materials have characteristics such as lightweight, high tensile strength and modulus to weight ratio, nonmagnetic and highly corrosion resistant. Many studies have shown that using plate-bonded technique, the performance of the strengthened concrete member was enhanced. In this technique, the surface preparation of concrete substrate and CFRP material along with the type of epoxy adhesive used are the critical factors affecting the bonding performance of the system. This paper discusses the experimental result on the bonding characteristics between CFRP plate and concrete. The bond stress was determined along the 200 mm bond length of the bonded CFRP plate to concrete. A 50 mm width by 1.6 mm thick CFRP plate was used and bonded to 100x100x300 mm concrete prism. The bonded CFRP plate to concrete prism was tested under tension-compression loads and the results have shown that at lower load level, the shear stress distribution along the bonded length was relatively linear and uniform. However, at higher load when micro cracking occurred along the lap joints the shear stress distribution became non-linear. The investigation on mode of failure of the sample shows that the bond between the CFRP plate and concrete was very good.